Effects of pre-storage treatments on sprouting and nutritional quality of ginger (zingiberofficinalerosc) rhizomes in different storage periods (2016)
Purpose: Ginger rhizomes are highly susceptible to damage during postharvest storage due to soil borne pathogenic disorder. Experiments were conducted to evaluate the effects of prestorage treatments required for sprouting and maintaining the quality of ginger plant in different storage periods at the Teaching and Research Farm, Ladoke Akintola University of Technology, Ogbomoso. Method: The rhizomes were treated with four different pre-storage treatments viz.,control, hydrated lime, - Mancozeb, and 100ml of Trichodermaharzianum solution at different storage periods of one, two and three months. The experiment was arranged in a complete randomized designand laid out in a randomized complete block design with three replicates. Data were collected on percentage sprouting, plant height, number of leaves, leaf area and nutritional quality of ginger rhizomes. Data were subjected to analysis of variance using Statistical Analysis System Software (SAS, 2005). Differences among treatment means were compared using Least Significance Difference (LSD) at 5% probability level. Results: The storage periods significantly (P≤0.05) influenced the percentage sprouting andgrowth parametersof ginger at various sampling period. Highest growth of 9.05cm was recorded from ginger plant stored for three months while the least value of 6.94cm was obtained from rhizomes stored for one month. The pre-storage treatments significantly (P≤0.05) influenced the percentage sprouting, weight loss and growth parameters of ginger at various sampling period. Highest percentage sprouting (94.3%) was recorded from rhizomes treated with 100 ml Trichodermaharzianim solution followed by rhizomes treated with hydrated lime (88.3 %) while lowest percentage sprouting (61.5 %) were recorded from control. Highest percentage weight loss of 46.3% was recorded from control followed by hydrated lime (35.58 %) while the lowest percentage weight loss of 33.93 % was recorded from 100 ml Trichodermaharzianim solution. Conclusions: In conclusion, rhizomes treated with Trichodermaharzianim solution for a period of three months before planting produced better sprouting and enhanced the growth quality of ginger on the field